Delivering Difficult News: Simulation-Enhanced Training Improves Psychiatry Residents' Clinical Communication Skills - Amsalem, Doron; Martin, Andrés; Mosheva, Mariela; Soul, Omer; Korotkin, Liran; Ziv, Amitai; Gothelf, Doron; Gross, Raz (Frontiers in Psychiatry, 2021)
Background: Delivering difficult news to individuals diagnosed with mental health disorders and their family members can be challenging. The use of simulated patients (SP) is an effective teaching method to enhance clinical skills, particularly those around communication. We developed, implemented, and evaluated the effectiveness of an SP-based training module to improve psychiatric residents’ clinical communication skills in delivering difficult news. Methods: We conducted 5-hour workshops consisting of three components: 1) a high-fidelity simulation session with a professional actor; 2) a 30-minute lecture; and 3) role-playing of three short scenarios, during which residents rotated taking on different roles (as psychiatrist, patient, or family member). We observed through a 1-way mirror and videotaped each resident’s simulation session and followed it with personalized debriefing. Following the workshop, each resident received the full-length video of their simulated interview, together with a list of questions as a take-home assignment. Two months after the workshop, the residents were invited to a second SP-based session, during which two independent evaluators, each a board-certified psychiatrist with expertise in medical simulation, evaluated the participants’ communication skills using a previously validated instrument. To avoid observation bias, the two evaluators rated the videotapes blind to the timing of the simulation (pre- vs post-training). Participants completed self-report questionnaires on satisfaction and self-confidence, before, after, and two months following the workshop. Findings: Of the 28 psychiatric residents who participated in the training day, 24 (86%) completed the post-workshop evaluation. Mean communication score increased from 24.9 to 27.8 (paired t-test: 5.6, p<.001). The mean score for the self-confidence questionnaire, calculated on a 1 to 5 Likert scale, increased from 3.4 to 4.0 after the training day, and remained unchanged (4.2) two months later (p<.001). Conclusions: An SP-based training module proved useful in improving the objectively measured communication skills of psychiatric residents delivering difficult news. The training further enhanced participants’ subjective sense of confidence in those clinical skills.